The Nexus between Foreign Direct Investment and Electricity Consumption in South Africa - Hlongwane, Nyiko Worship; Mahapa, Realeboga; Nthebe, Tselane Confidence (International Journal of Energy Economics and Policy, 2023)
The study investigates the nexus between foreign direct investment inflows and electricity consumption in South Africa. The study utilized borrowed time series data sourced from the World Bank and South African Reserve Bank spanning from 1970 to 2020. The study employs a Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) models to investigate the nexus between foreign direct investment inflows and electricity consumption in South Africa. The results of the Johansen cointegration test revealed the presence of cointegration relationships between the variables in the study. The results of the FMOLS and DOLS revealed negative statistically significant and insignificant relationship between electricity consumption and foreign direct investment inflows in South Africa, respectively. Other results revealed that economic growth has a positive statistically significant relationship with foreign direct investment inflows. The Granger causality results revealed unidirectional causality running from economic growth to foreign direct investment inflows. The study recommends that the government and policymakers must revise policies on electricity consumption and economic growth to attract foreign direct investment inflows in South Africa.